Quality of Carbon Emissions Disclosure on Corporate Sustainability Report Gojek Period 2020 and Goto Period 2021 – 2022 - Felicia Komala; Carmel Meiden (Journal Research of Social Science, Economics, and Management, 2024)
The high level of air pollution which is increasing from year to year causes air quality to decline. One of the causes of the increase in air is the growth in the number of motorized vehicles which causes an increase in the amount of emissions released in the form of Carbon Monoxide (CO), Hydrocarbons (HC), Nitrogen Oxide (NO). This shows that climate change is occurring. Climate change is one of the environmental problems that is currently of concern to stakeholders. The Carbon Disclosure Project (CDP) is a non-profit organization that operates focused on addressing environmental issues. CDP works by publishing information sheets which are useful as a guide for companies to disclose greenhouse gas (GHG) emissions resulting from the company's business activities. The company publishes a sustainability report which reveals carbon emissions. GoTo is a merger between Gojek and Tokopedia where in 2020 Gojek published a sustainability report. Scoring of carbon emission disclosures both quantitatively and qualitatively was carried out in this research. During the 2020-2021 period, the highest level of suitability and quality of disclosure was obtained by GoTo. Quantitatively, the climate change category has high disclosure quality. Qualitatively, the GHG emissions calculation category has the highest disclosure quality.